A Preference-Oriented Multi-Criteria Decision Model for Stunting-Prevention Food Basket Ranking using AHP-TOPSIS - Yaqin, Alvin Muhammad ‘Ainul; Rosyid, Mifthahul Janna; Leksono, Vridayani Anggi; Wantira, Amanda Dwi (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
It is necessary to give concentrated attention to the issue of stunting by implementing appropriate nutrition initiatives to prevent stunted physical and mental development. Optimal food availability is one effective strategy for preventing it. However, it often disregards preferences that guarantee pleasure, dietary diversity, and compatibility with individual tastes. In this paper, we show a two-step multi-criteria decision model. The AHP is used to figure out the criteria weights, and the TOPSIS method ranks food basket options based on how close they are to the ideal solution. The efficacy of our strategy was subsequently evaluated in Balikpapan, a prominent urban center in Indonesia grappling with the issue of stunting. The evaluation's findings were as follows: nutritional value (27%) was the most significant factor, knowledge of the food ingredients (18%), variety of foods made from the food ingredients (17%), ease of preparation, cooking, and storage (15%), cost (12%), and child preference (11%). The findings indicated that food basket 3, priced at Rp209,857 and yielding 1,854.96 kcal, consisted of rice weighing 3.63 kg, duck egg weighing 1.16 kg, milkfish weighing 0.65 kg, tuna weighing 0.06 kg, cauliflower weighing 0.17 kg, kale weighing 3.46 kg, and dragon fruit weighing 1.87 kg. In addition to nutrition and cost, this study highlights that considering preferences can enhance the appeal of food baskets.